Rekontruksi Ayat-ayat Akuntansi Syariah - Nurhadi Nurhadi (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This paper also tries to describe the values of wisdom and values of the Qur'an in natural accounting practices in sharia. One of the aspirations of the disclosure of these values was stated in the excavation of science in universities as HR regeneration in the field of sharia accounting. If the basis of revelation is of course the truth is in accordance with justice and human benefit. Therefore it is considered very necessary to reveal the basics of al-Qur'an revelation in confirming Islamic accounting knowledge, so that it is formed in full by reconstructing economic accounting verses. So the result is that the syariah accounting verses with the parent paragraph (Q.S (2): 282; (26): 181-184; (49): 6; (17): 35). Whereas there are 9 types of sharia accounting reporting principles, namely: Reported correctly (Q.S (10): 5); Quickly report (Q.S (2): 202; (3): 19; (5): 4; (13): 41); Created by experts (accountants) (Q.S (13): 21; (13): 40; (23): 117; (88): 26); Bright, clear, firm and informative (Q.S (17): 12; (14): 41; (84): 3); Contains comprehensive information (Q.S 6: 52; 39:10); Information is addressed to all parties involved horizontally and vertically (QS (2): 212; (3): 27; (3): 37; (13): 18; (13): 40; (24): 38; ( 38): 39; (69): 52); Detailed and thorough (Q.S (65): 8); No manipulation (Q.S (69): 20; (78): 27); Performed continuously (not negligent) (Q.S (21): 1).